OʻZBEKISTONNING ENG YANGI TARIXIGA DAXLDORLIK MASALASI - Azimov Muhammadi Azim o‘g‘li; Berdirasulova Shoxsanam Uchqunovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article analyzes the scientific and theoretical foundations of the issue of involvement in Uzbekistan’s modern history, its social and political aspects, and its role in society. Furthermore, by comparing it with the experiences of other countries, conclusions are drawn about how this process is unfolding in Uzbekistan. The significance of this study lies in the fact that it influences not only the formation of historical consciousness but also the attitude of future generations toward national heritage.